Prevalence of adult attention deficit hyperactivity disorder in patients of alcohol dependence syndrome: A cross-sectional study - Rishabh Singh; Kaushik Chatterjee; VS Chauhan (Industrial Psychiatry Journal)
Background: Alcohol use disorders (AUDs) are among the most common comorbid psychiatric disorders in patients with adult attention deficit hyperactivity disorder (ADHD), and adult ADHD is an independent risk factor for developing AUD. Aim: To study the prevalence of adult ADHD in patients with Alcohol dependence syndrome (ADS). Materials and Methods: In total, 177 cases of ADS diagnosed as per International Classification of Diseases-10, Diagnostic Criteria for Research (ICD-10, DCR) were included. The severity of alcohol dependence was estimated by the Severity of Alcohol Dependence Questionnaire (SADQ). The included patients were screened for adult ADHD by the Adult ADHD Self-Report Scale (ASRS-v1.1) symptom checklist, and statistical tests were applied. Results: Out of 177 patients with ADS, 21 patients screened positive for adult ADHD (11.9%). Greater severity of alcohol dependence among those screened positive for adult ADHD was noted compared to the adult ADHD negative group (P = 0.013). Adult ADHD-positive patients had an earlier age of onset of alcohol consumption (P = 0.020), higher mean duration of alcohol consumption (P < 0.001), and early onset of ADS (P = 0.038). ICD-10 criteria of loss of control, salience, and use despite harmful effects were significantly higher among the adult ADHD-positive group. Conclusion: The study findings suggest a significant prevalence of adult ADHD among patients with ADS.